Producción de textos escritos expositivos en estudiantes del quinto grado de educación secundaria en tres instituciones educativas públicas, distrito de Iquitos 2021 - Meza Pinedo, Alyssa Nadir (2023)
Research objective was: To establish differences in the level of production of expository written texts in fifth grade students of secondary education in three public educational institutions, in the Iquitos district - 2021, according to study shift. It is a comparative type of research, which included a sample of 268 subjects, a rubric was used to evaluate the study variable. The descriptive results showed that of the 58.2% of the students in the morning shift, 4.1% obtained a Good level; 28.0% Regular, and 26.1% Deficient. For their part, of the 41.8% of students in the late shift, 3.4% obtained a Good level; 16.0% Regular, and 22.4% Deficient. The results of the inferential analysis using the t-Student test, allowed to verify that there are statistically significant differences in the planning of expository written texts in students of the sample, according to study shift (p-value 0.01 < α =0.05). The results of the Mann–Whitney U test allowed us to verify that there are no significant differences in the textualization of expository written texts in students of the sample, according to the study shift (p-value .082 > α= 0.05). It was also verified that there are no significant differences in the revision of expository written texts in students of the sample, according to study shift (p-value .061 > α= 0.05). Finally, using the t-Student test, it was verified that there are statistically significant differences in the level of production of expository written texts in students, according to the study shift (p-value 0.01 < α =0.05).